2013
DOI: 10.1517/17425255.2013.788150
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and pharmacodynamics evaluation of ceftobiprole medocaril for the treatment of hospital-acquired pneumonia

Abstract: In patients with normal PK and non-VAP, ceftobiprole is effective for the treatment of HAP in the recommended doses, ceftobiprole is unlikely to achieve the desired PD targets when PK parameters are altered in VAP (e.g., increased volume of distribution and clearance). In these settings, off-label use at higher doses may overcome these limitations; but in the presence of alternative therapies, it cannot be currently recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The anti-MRSA cephalosporin ceftobiprole has been studied and approved only for skin and skin structure infections (SSSIs), 31 yet it is frequently used offlabel in some countries for ventilator-associated pneumonia (VAP) at these recommended doses despite indications that these are unlikely to achieve pharmacodynamic targets in patients with VAP. 32 In addition, the majority of currently used b-lactams underwent clinical outcome testing in Phase 3 trials several decades ago, when MICs for many organisms were lower. Longitudinal surveillance programmes document steady decreases in the susceptibility of several Gram-negative (Escherichia coli, Klebsiella spp., Pseudomonas aeruginosa etc.)…”
Section: Reviewmentioning
confidence: 99%
“…The anti-MRSA cephalosporin ceftobiprole has been studied and approved only for skin and skin structure infections (SSSIs), 31 yet it is frequently used offlabel in some countries for ventilator-associated pneumonia (VAP) at these recommended doses despite indications that these are unlikely to achieve pharmacodynamic targets in patients with VAP. 32 In addition, the majority of currently used b-lactams underwent clinical outcome testing in Phase 3 trials several decades ago, when MICs for many organisms were lower. Longitudinal surveillance programmes document steady decreases in the susceptibility of several Gram-negative (Escherichia coli, Klebsiella spp., Pseudomonas aeruginosa etc.)…”
Section: Reviewmentioning
confidence: 99%
“…However, at current dosing, conflicting data exist for the support of ceftobiprole use in VAP. Suggestions that ceftobiprole is unlikely to meet the desired pharmacodynamic targets when pharmacokinetic parameters are altered have been countered by Monte Carlo simulation based on phase 1 studies showing that target attainment is likely to be achieved, even in severely ill patients [121,122]. There needs to be a re-assessment of the quality of data for ceftobiprole use in SSTI, however the pneumonia data were of good quality.…”
Section: Ceftarolinementioning
confidence: 99%
“…However, β-Lactams are the most common cause of most antibiotics-associated adverse events, including severe kidney or liver toxicity, neurotoxicity, and cytopenia ( 59 ). One study showed a 2.5% incidence of gastrointestinal events with β-Lactam and a higher incidence of diarrhea when the above combination was used ( 60 ). More importantly, the β-Lactams assessed in this study included only first and second-generation cephalosporins, and no valid direct evidence could be produced to support the efficacy of the novel cephalosporins on OM.…”
Section: Discussionmentioning
confidence: 99%